Influence of Planting Scheme on the Growth Development of Rice Period in Seedling - Tursunov, Kh. O.; Juraeva, Kh. R.; Abduraimov, Sh. (Research Parks Publishing LLC, 2023)
Selection of some elements of technology of cultivation as a repeat cultivation in the seedlings of rice is determined by the choise of scientically-based varietes that meet the climatic condiyions and requirements of regions, their optimal number, their impact on the growth and growth of plant.